Collecting plant genetic diversity: Technical guidelines - Guarino, Luigi; Ramanatha Rao, V.; Reid, Robin S. (1995)
In recent years it has become evident that there is no single publication that provides the prospective collector of plant germplasm with generic as well as specific, and theoretical as well as practical, information. It was to fill this gap that IPGRI, together with FAO, IUCN and UNEP, cooperated to produce this book. The volume is a comprehensive reference work and is aimed at both new and experienced collectors as well as those with a general interest in plant genetics, breeding and biodiversity.